'THE HONEST TRADESMAN'S HONOUR': OCCUPATIONAL AND SOCIAL IDENTITY IN SEVENTEENTH-CENTURY ENGLAND*. (24th October 2014) - Hailwood, Mark
ABSTRACT: This paper starts from the proposition that historians of identity in the early modern period have paid insufficient attention to the significance of occupations and work. It demonstrates one possible approach to this topic by exploring the social identity of a particular occupational group – tradesmen – through a study of a particular source – printed broadside ballads. A number of important conclusions result: it argues that historians have overstated the dominance of craft-specific consciousness in the formation of early modern work-based identity (a term that is offered as a more helpful alternative to that of occupational identity), and suggests that broad-based identifiers such as 'tradesman' had a real purchase in contemporary discourse. It also considers the extent to which broader changes in the seventeenth-century economy – especially growing commercialisation and the increasing complexity of credit relations – affected the identity of the tradesman. Although the tension between the hard-working tradesman and the prodigal gentleman in ballad portraits suggests a growing social confidence on the part of the former, the marketplace is depicted to be as much a threat as an opportunity for tradesmen given the fragility of credit relationships. Moreover, the paper examines the gender dimensions of this occupational identity, arguing that a 'female voice' was central to ballad discussions of masculine ideals, and that the tradesman's patriarchal authority was generally portrayed as insecure. At its heart, the paper is an exploration of the intersection of class, gender and occupational identities in a period of economic change.